Fear conditioning and extinction across development: Evidence from human studies and animal models() - Shechner, Tomer (Biol Psychol, 2014)
The ability to differentiate danger and safety through associative processes emerges early in life. Understanding the mechanisms underlying associative learning of threat and safety can clarify the processes that shape development of normative fears and pathological anxiety. Considerable research has used fear conditioning and extinction paradigms to delineate underlying mechanisms in animals and human adults; however, little is known about these mechanisms in children and adolescents. The current paper summarizes the empirical data on the development of fear conditioning and extinction. It reviews methodological considerations and future directions for research on fear conditioning and extinction in pediatric populations.